Pathogenesis and Management of Intestinal Failure-Associated Liver Disease - Abi-Aad, Sasha-Jane; Lovell, Mark; Khalaf, Racha T.; Sokol, Ronald J. (Seminars in Liver Disease, 2025)
Long-term parenteral nutrition (PN) has considerably improved the management of intestinal failure (IF) in children and adults, particularly those with short bowel syndrome; however, it carries a significant risk of hepatotoxicity, specifically, intestinal failure-associated liver disease (IFALD), also known as PN-associated liver disease. This review provides an update on the latest understanding of IFALD pathogenesis, emerging therapies, and ongoing challenges in the management of this complication. A number of factors are associated with the development of IFALD. PN lipid emulsions, phytosterol exposure, bacterial dysbiosis, an altered gut–liver axis, and episodes of sepsis disrupt bile acid homeostasis and promote liver inflammation in the active phase of IFALD, favoring the development of PN-associated cholestasis (PNAC) and the more chronic form of steatohepatitis with fibrosis. Based on the identification of pathophysiological pathways, potential therapies are being studied in preclinical and clinical trials, including lipid emulsion modifications; targeted therapies such as Farnesoid X receptor (FXR) and liver receptor homolog 1 (LRH-1) agonists, tumor necrosis factor inhibitors, glucagon-like peptide-2 analogs; microbiome modulation; and supplementation with choline and antioxidants. In conclusion, the pathogenesis of IFALD is complex, and PN dependence and liver injury remain challenging, particularly in patients with IF who cannot advance to enteral nutrition and be weaned off PN.
Keywords: intestinal failure-associated liver disease; cholestasis; intestinal failure; lipid emulsions; parenteral nutrition-associated liver disease